The Magic of Randomization versus the Myth of Real-World Evidence - Collins, Rory; Bowman, Louise; Landray, Martin; Peto, Richard (The New England journal of medicine, 2020)
Nonrandomized observational analyses have been promoted as alternatives to randomized clinical trials. However, randomization ensures balance between groups, whereas nonrandomized studies are often biased by between-group differences. Efforts to reduce the cost and complexity of clinical trials are preferable to relying on observational studies.